Retrospective analysis of bevacizumab-induced arthralgia and clinical outcomes in ovarian cancer patients. Single center experience - Maria Kaparelou; Michalis Liontos; Pelagia Katsimbri; Aggeliki Andrikopoulou; Alikistis Papatheodoridi; Anastasios Kyriazoglou; Aristotelis Bamias; Flora Zagouri; Meletios Athanasios Dimopoulos (Elsevier, 2022)
Background: Joint manifestations are ill-defined adverse events that were frequently reported of bevacizumab in ovarian cancer patients. The aim of this study is to describe the incidence and severity of joint manifestations among bevacizumab treated patients as well as their relation to clinical outcomes. Methods: Medical charts of all ovarian cancer patients that received bevacizumab from 2012 through 2017 were reviewed. Joint manifestations were staged. Kaplan-Meier Survival curves were generated; survival differences were estimated. Results: 76 Patients diagnosed with stage III or IV ovarian cancer were included. 23 patients (30.3%) developed joint manifestations, 12 of them had Grade I, 4 Grade II and 7 Grade III. Only 3 patients developed arthritis. In 8 cases (34.8%) one joint was affected and in the remaining 15, multiple sites. Median number of bevacizumab cycles to arthralgia development was 7. 3 patients were managed with corticosteroids or methotrexate, all had grade 3 AEs. The remaining received common analgesics. Median duration of the AE was 4.8 months. 7 patients discontinued bevacizumab due to AE. In all but 3 patients AE was finally resolved. Median number of bevacizumab cycles received, frequency of treatment completion or treatment discontinuation due to disease progression did not differ significantly among patients that developed joint manifestations or not. Median PFS and median OS did not differ statistical significantly. Conclusion: Joint manifestations are common AEs in bevacizumab treated ovarian cancer patients and led to treatment discontinuation in 9% of the patients. However, this has not adversely affected the clinical outcome of the patients. Further research is needed for the appropriate management of these patients.